Micoplasmose e leucemia em felino - Assis, Cristina da Silva (Universidade Federal do Tocantins, 2022)
Currently, cats are popular and very well seen as companion pets. Due to the growing population of cats, there was a notorious spread of infectious agents and also of ectoparasites, causing several diseases among the feline population, and among them, mycoplasmosis or feline infectious anemia, the feline respiratory complex and feline viral leukemia. The main clinical signs related to these diseases are anemia, immunosuppression, apathy, progressive weight loss, respiratory desease, eye and oral problems, highlighting the importance of identifying and diagnosing infectious agents so that an effective treatment can be carried out, as they are diseases of common association involving pathogens that cause diverse and significant clinical signs and alterations in cats. This work is a case report attended during the mandatory curricular internship period at the University Veterinary Clinic of the Federal University of Tocantins, on the Araguaína campus, with the objective of obtaining the title of veterinarian, through the presentation of the reported clinical case, discussion with Literature basis and diagnostic conclusion. The internship began on September 14, 2021 and ended on November 17, 2021, under the guidance of Professor Dr. Priscilla Macedo de Souza and supervised by the veterinarian Dr. Flávia Augusta de Oliveira.